Sappho, the new “Brothers’ Poem” and its interpretation in the context of secondary sources and of Aeolian and hymnodic poetry (Circe de clásicos y modernos, 2022)
This article examines Sappho’s “Brothers’ Poem” in relation to fragments 5, 9 and 17 and to fragments 129 and 130b.17-20 of Alcaeus to determine the possible contexts of performance. It is established by critics that these fragments would have been hymns performed in the sanctuary of the Lesbian triad. The hymnodic character of these compositions leads to identify resonances in the corpus of Homeric Hymns (1, 7, 12 and 33) on the basis of invocations, epithets and spheres of influence that converge with those of the Aeolian lyric.
Keywords: Sappho; Brother's Poem; Alcaeus; Triad; Hymns